Long-Time Exposure to Violent Video Games Does Not Show Desensitization on Empathy for Pain: An fMRI Study - Gao, Xuemei; Pan, Wei; Li, Chao; Weng, Lei; Yao, Mengyun; Chen, Antao (Frontiers in Psychology, 2017)
As a typical form of empathy, empathy for pain refers to the perception and appraisal of others’ pain, as well as the corresponding affective responses. Numerous studies investigated the factors affecting the empathy for pain, in which the exposure to violent video games (VVG) could change players’ empathic responses to painful situations. However, it remains unclear whether exposure to VVG influences the empathy for pain. In the present study, in terms of the exposure experience to VVG, two groups of participants (18 in violent video game group, VG; 17 in non-violent video game group, NG) were screened from nearly 200 video game experience questionnaires. And then, the functional magnetic resonance imaging data were recorded when they were viewing painful and non-painful stimuli. The results showed that the perception of others’ pain were not significantly different in brain regions between groups, from which we could infer that the desensitization effect of violent video games was overrated.